Seminar Literasi Digital Sebagai Upaya Peningkatan Kecakapan Teknologi Dalam Membangun Masyarakat Digital di Desa Galihpakuwon Balubur Limbangan - Dinar Rahayu; Yopi Nugraha; Elin Rosliani (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
The development of technology has a significant impact on its users, provided that users can harness it effectively and wisely. This development and utilization of technology are closely tied to the use of the internet as a support for this technological use. In Indonesia, many people already use the internet in their daily activities; however, the level of digital literacy in Indonesian society is still at a moderate level. In the effort to realize a digital society, digital literacy has been discussed by various stakeholders and approached, but it has not been optimally implemented. A digital society is an example of a society where interaction patterns are greatly influenced by information technology and communication networks. The purpose of digital literacy activities is to enhance the technological skills of the community toward becoming a digital society. This digital literacy program is carried out through various methods, including literature review, observation, interviews, and problem analysis. Subsequently, a digital literacy seminar program is conducted in the village of Galihpakuwon Balubur Limbangan, which serves as the focal point of this initiative. The seminar content is tailored to the needs of participants in the context of existing issues, with a focus on digital literacy indicators such as Digital Skill, Digital Culture, Digital Ethics, and Digital Safety. The results achieved after this activity include the transformation of a traditional community into a digital community in the village of Galihpakuwon Balubur Limbangan.